Cine y televisión irlandeses – 2018 - Tony Tracy (Estudios Irlandeses, 2019)
In July 2018, the Irish Film Board announced that it was changing its name to Screen Ireland. It was done with relatively little fanfare or media attention and indeed still has to fully work through: as late as January 2019 Irish films were being simultaneously released into cinemas bearing alternately the Irish Film Board or Screen Ireland logos. Was this the year in review’s defining event or simply a timely re-branding? Either way, what might the change tell us? In announcing the change, a PR release explained that the new name reflects the agency’s “redefined, broadened remit, which has been driven both by the changing and diverse nature of the industry and audience content consumption. Screen Ireland is responsible for funding and promoting Irish film, TV and animation internationally, for skills development, and for promoting Ireland as a film location.” However, the wider remit also reflected the influence of the Department of Culture, Heritage and the Gaeltacht’s Audiovisual Action Plan (discussed by Roddy Flynn elsewhere), published a month earlier, which emphasised the need to augment support for film with a wider focus on television drama production and – potentially – digital games development as part of a decade-long strategy to develop Ireland as global hub for media production.